Sustainable Competitive Advantage through Strategic Analysis: A Case Study of PT Avia Avian Tbk - Shabrina Windy Cahyono (Publikasi Indonesia, 2026)
This study aimed to analyze the strategic factors that supported the creation of sustainable competitive advantage at PT Avia Avian Tbk, one of the leading companies in Indonesia’s paint and building coatings industry. The study employed a qualitative descriptive approach using a case study method, with secondary data obtained from the company’s annual reports, sustainability reports, official publications, and relevant scientific literature. The analysis was conducted using PEST analysis, Porter’s Five Forces analysis, industry life cycle analysis, value chain analysis, and the Competitive Profile Matrix (CPM). The findings indicated that PT Avia Avian Tbk maintained a strong competitive position supported by an extensive distribution network, product innovation capabilities, vertical integration, operational efficiency, and a commitment to sustainability. From an external environmental perspective, the company benefited from construction sector growth, increasing demand for environmentally friendly products, and technological developments that supported innovation. Meanwhile, competition within Indonesia’s paint industry remained relatively intense, although the threats posed by new entrants and substitute products were relatively low. The CPM results indicated that PT Avia Avian Tbk demonstrated a stronger competitive position compared with several major competitors in the industry. This study concluded that a company’s ability to manage internal resources, strengthen innovation, and adapt effectively to changes in the business environment were key factors in maintaining sustainable competitive advantage. The findings are expected to serve as a reference for manufacturing companies in formulating business strategies oriented toward long-term growth and sustainability.